Decellularized vascularized bone grafts: A preliminary in vitro porcine model for bioengineered transplantable bone shafts - Rougier, Guillaume; Maistriaux, Louis; Fievé, Lies; Xhema, Daela; Evrard, Robin; Manon, Julie; Olszewski, Raphael; Szmytka, Fabien; Thurieau, Nicolas; Boisson, Jean; Kadlub, Natacha; Gianello, Pierre; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction Durable reconstruction of critical size bone defects is still a surgical challenge despite the availability of numerous autologous and substitute bone options. In this paper, we have investigated the possibility of creating a living bone allograft, using the perfusion/decellularization/recellularization (PDR) technique, which was applied to an original model of vascularized porcine bone graft. Material and methods 11 porcine bone forelimbs, including radius and ulna, were harvested along with their vasculature including the interosseous artery and then decellularized using a sequential detergent perfusion protocol. Cellular clearance, vasculature, extracellular matrix (ECM), and preservation of biomechanical properties were evaluated. The cytocompatibility and in vitro osteoinductive potential of acellular ECM were studied by static seeding of NIH-3T3 cells and porcine adipose mesenchymal stem cells (pAMSC), respectively. Results The vascularized bone grafts were successfully decellularized, with an excellent preservation of the 3D morphology and ECM microarchitecture. Measurements of DNA and ECM components revealed complete cellular clearance and preservation of ECM’s major proteins. Bone mineral density (BMD) acquisitions revealed a slight, yet non-significant, decrease after decellularization, while biomechanical testing was unmodified. Cone beam computed tomography (CBCT) acquisitions after vascular injection of barium sulphate confirmed the preservation of the vascular network throughout the whole graft. The non-toxicity of the scaffold was proven by the very low amount of residual sodium dodecyl sulfate (SDS) in the ECM and confirmed by the high live/dead ratio of fibroblasts seeded on periosteum and bone ECM-grafts after 3, 7, and 16 days of culture. Moreover, cell proliferation tests showed a significant multiplication of seeded cell populations at the same endpoints. Lastly, the differentiation study using pAMSC confirmed the ECM graft’s potential to promote osteogenic differentiation. An osteoid-like deposition occurred when pAMSC were cultured on bone ECM in both proliferative and osteogenic differentiation media. Conclusion Fully decellularized bone grafts can be obtained by perfusion decellularization, thereby preserving ECM architecture and their vascular network, while promoting cell growth and differentiation. These vascularized decellularized bone shaft allografts thus present a true potential for future in vivo reimplantation. Therefore, they may offer new perspectives for repairing large bone defects and for bone tissue engineering.